1988
DOI: 10.1177/036354658801600313
|View full text |Cite
|
Sign up to set email alerts
|

The effect of differential training on isokinetic muscular endurance during acute thermally induced hypohydration

Abstract: The purpose of this study was to test the effect of acute thermal hypohydration on the muscle endurance performance of three groups of differentially trained subjects. Group I consisted of six anaerobically trained athletes, Group II consisted of five aerobically trained athletes, and Group III consisted of six sedentary individuals. Experimental trials involved maximal leg extensions performed on a Cybex II dynamometer under conditions of euhydration and hypohydration of minus 3% body weight. Integrated elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
2

Year Published

1989
1989
2015
2015

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 29 publications
1
11
0
2
Order By: Relevance
“…Of these, 28 [7, 8, 11-14, 17-20, 24, 25, 30-45] met all of the inclusion criteria, thereby producing a total of 85 individual studies and weighted mean treatment effects to investigate the impact of hypohydration on upper (6/85) and lower (10/85) body muscle endurance, upper (14/85) and lower (25/85) body muscle strength, muscle anaerobic power (9/85) and capacity (9/85), and vertical jumping ability (12/85). A total of 20 research manuscripts produced more than one weighted mean treatment effect, with Hayes and Morse [25] producing ten, Ftaiti et al [34] producing two, Wilson et al [45] two, Cheuvront et al [17] two, Bigard et al [8] two, Bijlani and Sharma [30] two, Bosco et al [31] two, Bosco et al [32] six, Caterisano et al [33] three, Greiwe et al [35] four, Gutierrez et al [36] six, Jacobs [37] six, Jones et al [13] two, Judelson et al [11] six, Kraft et al [38] two, Montain et al [39] two, Naharudin and Yusof [40] six, Periard et al [41] four, Viitasalo et al [44] four, and Webster et al [12] four effect estimates. The work of Naharudin and Yusof [40] and Caterisano et al [33] contained three different groups of participants, while that of Gutierrez et al [36] contained two different groups of participants.…”
Section: Search Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of these, 28 [7, 8, 11-14, 17-20, 24, 25, 30-45] met all of the inclusion criteria, thereby producing a total of 85 individual studies and weighted mean treatment effects to investigate the impact of hypohydration on upper (6/85) and lower (10/85) body muscle endurance, upper (14/85) and lower (25/85) body muscle strength, muscle anaerobic power (9/85) and capacity (9/85), and vertical jumping ability (12/85). A total of 20 research manuscripts produced more than one weighted mean treatment effect, with Hayes and Morse [25] producing ten, Ftaiti et al [34] producing two, Wilson et al [45] two, Cheuvront et al [17] two, Bigard et al [8] two, Bijlani and Sharma [30] two, Bosco et al [31] two, Bosco et al [32] six, Caterisano et al [33] three, Greiwe et al [35] four, Gutierrez et al [36] six, Jacobs [37] six, Jones et al [13] two, Judelson et al [11] six, Kraft et al [38] two, Montain et al [39] two, Naharudin and Yusof [40] six, Periard et al [41] four, Viitasalo et al [44] four, and Webster et al [12] four effect estimates. The work of Naharudin and Yusof [40] and Caterisano et al [33] contained three different groups of participants, while that of Gutierrez et al [36] contained two different groups of participants.…”
Section: Search Resultsmentioning
confidence: 99%
“…Of these, 129 were considered trained [11, 12, 18, 24, 32-34, 36, 37, 40-42, 44] and 155 untrained [7,8,13,14,17,19,20,25,30,31,33,35,38,39,43,45]. Their physical characteristics are presented in Table 2.…”
Section: Description Of Participantsmentioning
confidence: 99%
“…Studies examining muscular endurance have shown signiWcant impairment (Bosco et al 1974;Caterisano et al 1988;Montain et al 1998;Torranin et al 1979) and no diVerence (Caterisano et al 1988;Ftaiti et al 2001;Greiwe et al 1998). Inconsistent Wndings may relate to methodological diVerences in mode of mass reduction (passive/active, diuretic, and caloric restriction), level of dehydration, and testing protocols.…”
Section: Introductionmentioning
confidence: 99%
“…Dehydration (Buskirk et al 1958;Jacobs 1980), hypohydration (Caterisano et al 1988;Caldwell et al 1984), and plasma volume lois negatively affect work capacity (Coppin et al 1978;Craig and Cummings 1966;53itin 1964).…”
Section: Introductionmentioning
confidence: 99%
“…Cold exposure (10*C to 18*C) compounds the problems associated vith immersion diuresis by causing loss of muscular power and strength (Bergh 1980;Caterisano et al 1988;Gilmour and Edwards 1986), loss of mental faculties (Vaughan 1975;Vaughan 1977), and possible death due to severe hypothermia.…”
Section: Introductionmentioning
confidence: 99%